2017
DOI: 10.1080/13546805.2017.1418306
|View full text |Cite
|
Sign up to set email alerts
|

Category fluency in schizophrenia: opposing effects of negative and positive symptoms?

Abstract: This is the first study showing that positive symptoms are related to increased fluency performance when disorganisation is controlled for. Like previous studies, negative symptoms were found to depress fluency. Strategy measures indicated that negative symptoms predispose for rigidity, whereas positive symptoms facilitate more efficient associative pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…These reported differences may be driven by the variety of the presented stimuli as well as the presence of formal thought disorder symptomatology. Previous studies found verbal fluency deficits in both negative (Joyce et al, 1996) and positive formal thought disorder (Goldberg et al, 1998), as well as contradicting results, showing that positive symptoms were positively related to semantic fluency (Egeland et al, 2018). Correlation analysis in the current study showed that only negative formal thought disorder -often referred to as alogia or poverty of speech -was adversely related with performance on semantic fluency.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…These reported differences may be driven by the variety of the presented stimuli as well as the presence of formal thought disorder symptomatology. Previous studies found verbal fluency deficits in both negative (Joyce et al, 1996) and positive formal thought disorder (Goldberg et al, 1998), as well as contradicting results, showing that positive symptoms were positively related to semantic fluency (Egeland et al, 2018). Correlation analysis in the current study showed that only negative formal thought disorder -often referred to as alogia or poverty of speech -was adversely related with performance on semantic fluency.…”
Section: Discussioncontrasting
confidence: 97%
“…Additionally, traditional diagnostic procedures of verbal fluency output analyze responses with respect to the number of correctly generated words only. To identify the underlying problem of limited output in verbal fluency in schizophrenia, it might be beneficial to use additional procedures to analyze word generation performance such as clustering and switching component scores (Bozikas, Kosmidis & Karavatos, 2005;Egeland et al, 2018;Robert et al, 1998) as well as temporal parameters (Docherty et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical correlation of antisaccade data with clinical features showed that antisaccade latencies were related to negative symptoms and social functioning, such that slower responses were related to more negative symptoms and more impaired social functioning across the psychosis spectrum. Antisaccade variables may be useful as proxy measures of persistent deficits in cognitive, social, motivational and emotional features (Egeland, Holmen, Bang-Kittilsen, Bigseth, & Engh, 2018; Grant & Beck, 2009; Green, 1996; Rector, Beck, & Stolar, 2005), an empirical question for future testing.…”
Section: Discussionmentioning
confidence: 99%
“…Phonemic VF deficits have additionally been related to negative symptoms ( Ojeda et al, 2010 ). Deficits in semantic VF, on the other hand, have been associated with both positive FTD ( Egeland et al, 2018 ) and—mediated by cognitive speed (as measured by the Digit Symbol Substitution Test ; Wechsler, 1997 )—alogia ( Brébion et al, 2018 ) as well as with disease duration ( Ojeda et al, 2010 ). Semantic tasks furthermore revealed above-average production of early acquired words with high typicality (expressed as percentage values based on normed data from categorization tasks) ( Juhasz et al, 2012 ).…”
Section: Current Clinical Findingsmentioning
confidence: 99%